Effects of Mediterranean Diet or Low-Fat Diet on Blood Fatty Acids in Patients with Coronary Heart Disease. A Randomized Intervention Study - Monica Gianna Giroli (Nutrients, 2021)
The Mediterranean diet (MD) prevents cardiovascular disease by different putative mechanisms, including modifications in the blood fatty acid (FA) profile. Polytherapy for secondary cardiovascular prevention might mask the effect of MD on the FA profile. This study was aimed to assess whether MD, in comparison with a low-fat diet (LFD), favorably modifies the blood FA profile in patients with coronary heart disease (CHD) on polytherapy. One hundred and twenty patients with a recent history of coronary stenting, randomized to MD or to LFD, completed 3 months of this open-label dietary intervention study. Diet Mediterranean-ness was evaluated using the Mediterranean Diet Adherence Screener (MeDAS) score. Both diets significantly reduced saturated FA (p < 0.01). Putative favorable changes in total n-3 FA (p = 0.03) and eicosapentaenoic acid plus docosahexaenoic acid (EPA + DHA; p = 0.04) were significantly larger with MD than with LFD. At 3 months, in the whole cohort, the MeDAS score correlated inversely with palmitic acid (R = −0.21, p = 0.02), and with palmitoleic acid (R = −0.32, p = 0.007), and positively with total n-3 FA (R = 0.19, p = 0.03), EPA (R = 0.28, p = 0.002), and EPA + DHA (R = 0.21, p = 0.02). In CHD patients on polytherapy, both MD and LFD shift FA blood composition towards a healthier profile, with a more favorable effect of MD on omega−3 levels.